A comparison of methods to teach foreign‐language targets to young children. Issue 1 (12th February 2019) - Matter, Ashley L.; Wiskow, Katie M.; Donaldson, Jeanne M.
Abstract : Using instructional strategies based on derived relational responding (DRR) to teach foreign‐language targets may result in emergent, untrained foreign‐language relations. One benefit of using DRR instructional strategies is the efficiency with which an individual acquires additional stimulus relations as a result of emergent responding following acquisition of one or a small number of relations. In the current study, we compared the efficiency of tact training alone to a traditional foreign‐language teaching strategy (i.e., teaching all relations concurrently—mixed training) with four, 4‐year‐old children. The results demonstrated that tact training was more efficient than mixed training for 5 of 7 stimulus sets. The findings add to the research demonstrating that DRR instructional strategies, specifically tact training, may be more efficient than concurrently teaching all targeted relations.